PENDAMPINGAN PENYAMAAN PERSEPSI DESA WISATA PADA PENGELOLA DESA WISATA SANEO KABUPATEN DOMPU - Muhammad Sultan Hali; Ramdah Radjab; Firman Koma Febdilan; Ayu Gardenia Lantang; Muhammad Adieb Hidayatullah; Muhammad Amar; Krismon Nusantara Saksi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The management of Saneo Tourism Village, perception alignment activities aim to create a harmonious understanding among the community, tourism village managers, and the local government. A participatory approach is used at every step of the process: identifying needs and potentials, conducting observations, holding focus group discussions (FGDs), and socializing. Evaluation methods are used to determine the effectiveness of the activities, ensure that perceptions are aligned, and create strategic follow-ups. As a result of the activities, participants gained a better understanding of the vision, mission, roles, and community-based management strategies. To achieve the village's vision as a sustainable community-based destination, capacity building for the community, environmental and cultural preservation, digital promotion, and the formulation of a joint action plan, the evaluation shows that the strategies used are very effective, and recommendations for enhancing cooperation and further training